Representasi Sembahyang dalam Puisi Ketika Engkau Bersembahyang Karya Emha Ainun Nadjib dan Sajadah Panjang Karya Taufiq Ismail - Ramadhan, Putri Maharani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Prayer is one of the obligations that must be carried out by a Muslim. Taufiq Ismail and Emha Ainun Nadjib are writers who include religious elements in their works. This research aims to provide a description of prayer in the poetry of the two writers. The method used in this research is descriptive qualitative method and comparative literature study. The poems Sajadah Panjang and Ketika Engkau Bersembahyang have similarities. However, besides the similarities, these two poems have differences in describing prayer.